Design of controlled multi-probe coupled assay via bioinspired signal amplification approach for mercury detection. Issue 63 (17th June 2016) - Mubarok, Ahmad Zaki; Lin, Szu-Ting; Mani, Veerappan; Huang, Chih-Hung; Huang, Sheng-Tung
Abstract : A bioinspired signal amplification approach is reported for mercury ion detection: a proof-of-concept. Abstract : We have designed and synthesized off–on fluorometric probes, 7-(but-3-yn-1-yloxy)-8-(difluoromethyl)-2 H -chromen-2-one (AYF) and 7-((4-( tert -butyldiphenylsilyloxy)benzyl)oxy)-8-(difluoromethyl)coumarin (DPF1 ), by incorporating the concept of biological signal transduction strategy into their molecular design and present their proof-of-concept demonstration for mercury (Hg 2+ ) detection. AYF undergoes a cascade of self-immolative reactions in the presence of Hg 2+ and unmasks fluorogenic coumarin1 and releases two latent fluoride ions. These fluorides initiate the removal of silyl protecting trigger group on DPF1 which directs another cascade of self-immolative reactions. The fluoride ions (amplifiers) are continuously activating the cascade reaction, and, as a result, coumarin1 progressively accumulates in the reaction medium and the whole process accelerates an amplified signal for Hg 2+ . For detection of Hg 2+, the limit of detection of the two-probe coupling assay (AYF and DPF1 ) is 0.51 ppb which is more than 2000 times lower than that of AYF alone. Besides, 3-(benzothiazol-2-yl)-4-carbonitrile-7-((4-( tert -butyldiphenylsilyloxy)benzyl)oxy)coumarin (DCC), a long-wavelength probe, was coupled with AYF and DPF1 in order to shift the emission to a higher wavelength region. Negative control studies revealed that the probes undergo controlled and organized sensing pathways as we designed.